2022
DOI: 10.1021/acsnano.2c03993
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive, Antibacterial, and Reductive Nanogels as a Mucolytic Agent for Efficient Nebulized Therapy to Combat Allergic Asthma

Abstract: Asthma is an intractable disease involving the infiltration of inflammatory cells and mucus plugging. Despite small molecular mucolytics having the ability to break the disulfide bonds of mucins, offering a potential way to overcome the airflow obstruction and airway infection, these mucolytics have limited therapeutic effects in vivo. Therefore, in this work, arginine-grafted chitosan (CS-Arg) is ionically cross-linked with tris(2-carboxyethyl)phosphine (TCEP) to obtain nanogels as a mucolytic agent. The posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Compared with PEI, three different characteristic peaks in N 1s spectra at 398. [31] The mentioned experimental results demonstrated that Arg successfully conducted the amidation reaction with PEI. Subsequently, the mediator cross-linker TCEP was added to the system, and the 3D cross-linked binder PAT was obtained.…”
Section: Resultsmentioning
confidence: 88%
“…Compared with PEI, three different characteristic peaks in N 1s spectra at 398. [31] The mentioned experimental results demonstrated that Arg successfully conducted the amidation reaction with PEI. Subsequently, the mediator cross-linker TCEP was added to the system, and the 3D cross-linked binder PAT was obtained.…”
Section: Resultsmentioning
confidence: 88%
“…Mouse embryonic fibroblast (NIH-3T3) cells received from Chen's group 41 were used to evaluate the in vitro cytotoxicity of the hydrogel. First, the test extract was prepared by immersing the hydrogel in DMEM (3 cm 2 mL −1 ) containing 10% FBS, 100 μg mL −1 streptomycin and penicillin, and 1% l -glutamine at 37 °C for 24 h. The extract (100%) was diluted with DMEM to 10% and 1% of the original.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al developed a nanogel as a mucolytic agent for the treatment of asthma. [81] This nanogel, which consists of argininegrafted chitosan and tris(2-carboxyethyl)phosphine (TCEP), can be administered via a nebulizer. The nanogel prevented the aggregation of mucin, i.e., the cause of mucus clogging in the nasal cavity and elsewhere, via two types of actions, i.e., the electrostatic interaction at the chitosan moiety and disulfide bond cleavage by TCEP, which effectively inhibited the growth of two bacterial species.…”
Section: Photothermal and Photodynamic Therapymentioning
confidence: 99%